2011
DOI: 10.1152/ajprenal.00024.2010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of heme oxygenase augments tubular sodium reabsorption

Abstract: Jackson KE, Jackson DW, Quadri S, Reitzell MJ, Navar LG. Inhibition of heme oxygenase augments tubular sodium reabsorption. Am J Physiol Renal Physiol 300: F941-F946, 2011. First published February 2, 2011 doi:10.1152/ajprenal.00024.2010.-Heme oxygenase (HO) catalyzes the degradation of heme to form iron, biliverdin, and carbon monoxide (CO). The vascular actions of CO include direct vasodilation of vascular smooth muscle and indirect vasoconstriction through inhibition of nitric oxide synthase (NOS). This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
2
15
1
Order By: Relevance
“…Recently, we reported that HO inhibition promotes sodium and/or water retention and decreases urine flow without significant differences in haemodynamic function . However, in the present study we demonstrated changes in haemodynamic function without any differences in urine flow.…”
Section: Discussioncontrasting
confidence: 86%
“…Recently, we reported that HO inhibition promotes sodium and/or water retention and decreases urine flow without significant differences in haemodynamic function . However, in the present study we demonstrated changes in haemodynamic function without any differences in urine flow.…”
Section: Discussioncontrasting
confidence: 86%
“…The HO inhibitor chromium mesoporphyrin decreased renal HO-1 and CO but did not affect RBF or GFR or NO production in the rat (718). In another study, HO inhibition increased RVR in the rat kidney which was more pronounced when NOS was inhibited (1242).…”
Section: Carbon Monoxidementioning
confidence: 88%
“…Changes in renal cortical and medullary blood flow were determined by laser flowmeter (Advance Laser Flowmeter ALF 21D, Tokyo, Japan) as described earlier [1617]. Glomerular filtration rate (GFR) was measured based on inulin clearance as previously described [1819].…”
Section: Methodsmentioning
confidence: 99%